BASIS OF ESTABLISHMENT AND REORGANIZATION OF HIGHER EDUCATION ORGANIZATIONS (World Bulletin of Management and Law, 2025)
This article examines the foundations of the formation of higher education organizations in accordance with the principles of organization and reorganization in accordance with civil law. In addition, this article presents the foundations of regulatory legal acts that are the legal basis for the formation and reorganization of higher education organizations.